Role of CYP2D6 Polymorphisms in the Outcome of Postoperative Pain Treatment. Issue 10 (19th May 2015) - Seripa, Davide; Latina, Paola; Fontana, Andrea; Gravina, Carolina; Lattanzi, Monia; Savino, Maria; Gallo, Antonietta P.; Melchionda, Giuseppe; Santini, Stefano A.; Margaglione, Maurizio; Copetti, Massimiliano; di Mauro, Lazzaro; et al.
Abstract: Objective: To investigate the role of CYP2D6 phenotype in the outcome of postoperative (PO) pain (POP) treatment. Design: Longitudinal cohort study. Open‐label trial with post hoc analysis. Setting: General Hospital Surgery and Recovery Units. Patients: Ninety unrelated Caucasians submitted to abdominal/thoracic surgery. Interventions: Standard multimodal POP treatment including opioids (tramadol) and nonsteroidal anti‐inflammatory drugs (ketoprofen) at different dosages and infusion rates according to the predicted mild, moderate, or severe POP. Outcome Measures: Pain (Numeric Rating Scale—NRS) and sedation (Ramsay Sedation Scale—RSS) up to 24 hours after surgery. By genotyping 16 CYP2D6 alleles, the four CYP2D6 phenotypes poor metabolizer (PM), intermediate metabolizers (IM), extensive metabolizers (EM) and ultrarapid metabolizers (UM) were predicted. Results: As compared with the CYP2D6‐EM phenotype, in the early PO time (30 min) a higher RSS mean score in IM was observed ( P  = 0.035). A suggestion towards higher mean score in PM ( P  = 0.091) and a minor mean score in UM ( P  = 0.091) was also detected. No difference in the outcome of pain across the CYP2D6 phenotypes was observed. Conclusions: In respect to the normal CYP2D6 phenotype, our results suggested that slowly metabolizers (IMs and PMs) might have a major sedation, whereas more rapid metabolizers (UM) a minor sedation, in the early time after surgery. A minor role of CYP2D6 phenotype in PO analgesia may be suggested.